2012
DOI: 10.1016/j.ijom.2011.07.1070
|View full text |Cite
|
Sign up to set email alerts
|

Soft tissue stability in segmental distraction of the anterior mandibular alveolar process. A 2-year follow-up

Abstract: This study evaluated soft tissue changes in adult patients treated with distraction osteogenesis (DOG) of the anterior mandibular alveolar process and related it to different parameters. 33 patients (27 females; 6 males) were analysed retrospectively before surgery at T1 (17.0 days), after surgery at T2 (mean 6.5 days), at T3 (mean 24.4 days), and at T4 (mean 2.0 years). Lateral cephalograms were traced by hand, digitized, superimposed, and evaluated. Statistical analysis was carried out using Kolmogorov-Smirn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…In the authors' previous study on 33 patients 2.0 years postoperatively, the net effect of the soft tissue at point B 0 was 100% of the advancement at point B while the lower lip (labrale inferior) followed the advancement of incision inferior to 46%. 13 The effects of ageing and soft tissue elasticity have to be considered when analysing long-term effects of maxillofacial surgery on the lips and chin. In his longitudinal Table 4 and labrale inferior could be the missing data from the 16 patients who could not be re-examined for the 5.5 year follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the authors' previous study on 33 patients 2.0 years postoperatively, the net effect of the soft tissue at point B 0 was 100% of the advancement at point B while the lower lip (labrale inferior) followed the advancement of incision inferior to 46%. 13 The effects of ageing and soft tissue elasticity have to be considered when analysing long-term effects of maxillofacial surgery on the lips and chin. In his longitudinal Table 4 and labrale inferior could be the missing data from the 16 patients who could not be re-examined for the 5.5 year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The removal of the miniplates could have led to a slight increase in soft tissue change (T4-T3) of point B 0 . 13 In addition, the interface of the surgical section of the anterior aspect of the symphysis was more susceptible to resorption and bony remodelling. 2,14 In conclusion, this long-term follow-up of 5.5 years found that further change in soft tissues occurred between 2.0 and 5.5 years postoperatively regarding point B 0 and labrale inferior.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6 Recently, changes in skeletal stability, and soft tissue profile were analysed after DO of the anterior alveolar process. 7,8 Besides the clinical benefits of DO, complications such as neurosensory disturbances of the inferior alveolar nerve are possible. Neurosensory changes in the alveolar nerve were evaluated mainly in animal studies after DO of the whole mandible.…”
mentioning
confidence: 99%